Iridescence untwined: honey bees can separate hue variations in space and time. (7th June 2022) - Ng, Leslie; Ospina-Rozo, Laura; Garcia, Jair E; Dyer, Adrian G; Stuart-Fox, Devi
Abstract: Iridescence is a phenomenon whereby the hue of a surface changes with viewing or illumination angle. Many animals display iridescence but it currently remains unclear whether relevant observers process iridescent color signals as a complex collection of colors (spatial variation), or as moving patterns of colors and shapes (temporal variation). This is important as animals may use only the spatial or temporal component of the signal, although this possibility has rarely been considered or tested. Here, we investigated whether honey bees could separate the temporal and spatial components of iridescence by training them to discriminate between iridescent disks and photographic images of the iridescent patterns presented by the disks. Both stimuli therefore contained spatial color variation, but the photographic stimuli do not change in hue with varying angle (no temporal variation). We found that individual bee observers could discriminate the variable patterns of iridescent disks from static photographs during unrewarded tests. Control experiments showed that bees reliably discriminated iridescent disks from control silver disks, showing that bees were processing chromatic cues. These results suggest that honey bees could selectively choose to attend to the temporal component of iridescent signals to make accurate decisions. Abstract : Many organisms have iridescent patches that are beautifully complex to animal observers - their colors change across both space and time. We show that animals can use these components separately, by training bees to choose discs that change color over time while ignoring those that only change across space. The temporal change can be important for animals with a flashy signal, while a spatial mosaic of colors could be more important for other animals.